Towards Simulation of CubeSat Operational Scenarios under a Cyber-Physical Systems View - de Almeida, Danilo Pallamin; Graics, Bence; Chagas, Ronan Arraes Jardim; de Sousa, Fabiano Luis; Mattiello-Francisco, Fatima (Anais do Workshop on Validation and Verification of Future Cyber-physical Systems (WAFERS), 2021)
In the development of academic CubeSat-based space missions, it is common to skip or rush many practices of the Systems Engineering Process due to time and cost constraints, which may lead to issues later on in the mission and failures. Mission concept analyses are often in these practices, including the analysis of the in-orbit behavior of the satellite with respects to power consumption and data generation. With the purpose of supporting these analyses, this article introduces a workflow based on a Cyber-Physical abstraction of CubeSat mission operation scenarios, which uses architectural models based on SysML Class Diagrams and automatic model transformation to support the simulation of these operational scenarios in an open source Model-Based System Engineering (MBSE) tool. These simulations can be used in mission concept analyses in Phase-0 studies to verify initial operations requirements and drive further design implementations.